PENGARUH FINANCIAL DISTRESS, AUDIT DELAY DAN OPINI AUDITOR TERHADAP AUDITOR SWITCHING - Susana Dewi; Farhan Fadilah; Edi Sutanto (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to determine whether financial distress, audit delay, and audit opinion significantly affect partial and simultaneous auditor switching in transportation and logistiks sector companies listed on the Indonesia Stock Exchange in 2018-2022. The data in this study uses secondary data in the form of audited financial reports obtained through the Indonesia Stock Exchange website www.idx.co.id, and the sampling technique uses purposive sampling to produce a total sample of 12 companies. For data analysis techniques using, descriptive statistical analysis, logistik regression model feasibility test, logistik regression model analysis, and hypothesis testing. The results showed that audit delay partially has a significant effect on auditor switching, while financial distress and audit opinion partially have no significant effect on auditor switching. In addition, the results show that simultaneously financial distress, audit delay, and audit opinion affect auditor switching.